Does Hypertension affect Saliva Properties? - Mohiti, Azra (J Dent (Shiraz), 2020)
STATEMENT OF THE PROBLEM: Systemic conditions can affect the salivary glands and oral health. Hypertension induces xerostomia. Because the function of saliva is related to its quality and quantity, therefore, any changes in saliva can lead to diminished quality of patient’s life. PURPOSE: The aim of this study was to determine the relationship between pH and viscosity of cumulative unstimulated saliva and hypertension in adults with sustained hypertension. MATERIALS AND METHOD: This cross sectional study took place on patients referred to oral medicine faculty of Shahid Sadoughi University of Medical Science. The patients’ blood pressure was measured and the 135 patients fitting the inclusion criteria participated in the study. Their unstimulated cumulative saliva was collected by spitting method and pH of the samples was measured by digital pH-meter set. The viscosity of the samples was measured by comparing the amount of saliva displacement in the thistle tube with control fluids at mm/10 seconds. The data was analyzed by SPSS version 20 software and ANOVA tests and Tukey multiple comparison and their nonparametric equivalent (p≤ 0.005). RESULTS: The results of this study showed that there was a significant relationship between pH and viscosity of unstimulated saliva of normotensive and borderline hypertensive patients (p<.0001and p< .005, respectively) and between normotensive and stage I hypertensive patients (p<.0001, p<0.000). Therefore, hypertension had a direct and significant relationship with saliva viscosity but a reverse relationship with saliva pH. CONCLUSION: Hypertension can reduce the pH and increase the salivary viscosity in hypertensive patients, which subsequently lead to changes in quality and quantity of secreted saliva and influence the oral health and quality of the patient’s life.